Pengaruh Manajemen Kepala Sekolah dan Efektivitas Media Pembelajaran Guru Terhadap Prestasi Belajar Siswa Di SMK Al Muawanah Gunungsari Kabupaten Serang (Study Kasus di SDM Al Muawanah Gunung Sari Kabupaten Serang) - Maman Suratman; Ressa Nurdiana; Dian Wirtadipura (Amal Insani Foundation, 2023)
The purpose of this study was to determine: 1) the effect of management principals on student achievement in SMK Al Muawanah Gunungsari; 2) The effect of instructional media on student achievement in SMK Al Muawanah Gunungsari; 3) The effect of management principals and instructional media on student achievement in SMK Al Muawanah Gunungsari. This research is quantitative research with observational design. Targets to be studied is the contribution of the management principals and instructional media for Student Achievement in SMK Al Muawanah Gunungsari. The population in this study are all teachers at SMK Al Muawanah Gunungsari add up District 51 people and all of them were taken samples with total sampling technique. Collecting data using questionnaires. Data analysis techniques used by multiple regression analysis, t test, F test and coefficient ofdetermination. The study concluded that: 1) There is a positive and significant influence between management principals on student achievement in SMK Al Muawanah Gunungsari (rX1Y = 0.519; t = 4.246; p = 0.000); 2) There is a positive and significant influence between learning media on student achievement in SMK Al Muawanah Gunungsari (rX2Y = 0.474; t = 3.769; p = 0.000); 3) There is significant influence simultaneously between management principals and instructional media on student achievement in SMK Al Muawanah Gunungsari (RX1X2Y = 0.595; Fhit = 13.155; p = 0.000).